2018
DOI: 10.1186/s12944-018-0839-9
|View full text |Cite
|
Sign up to set email alerts
|

A study of ghrelin and leptin levels and their relationship to metabolic profiles in obese and lean Saudi women with polycystic ovary syndrome (PCOS)

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is considered as one of the most frequently encountered hormonal pathologies in women during their reproductive years. Leptin and ghrelin, peptide hormones with adipostatic and orexigenic effect, respectively, seem to be involved in the metabolic changes that occur in PCOS. The aim of this study was to determine serum ghrelin and leptin levels in obese and lean Saudi women with PCOS and to investigate their relationship to the metabolic profiles in these women.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
4
27
1
Order By: Relevance
“…As previously mentioned, in our study, we did not find any significant differences in leptin and ghrelin concentrations between the PCOS patients and the control group. These results support the previous findings of other studies, which presented similar leptin and ghrelin levels in both PCOS patients and control group [ 59 ]. Contradictory results have been reported by Pekhlivanov et al [ 60 ] and Jalilian et al [ 61 ], who noted increased leptin concentrations in PCOS patients.…”
Section: Discussionsupporting
confidence: 93%
“…As previously mentioned, in our study, we did not find any significant differences in leptin and ghrelin concentrations between the PCOS patients and the control group. These results support the previous findings of other studies, which presented similar leptin and ghrelin levels in both PCOS patients and control group [ 59 ]. Contradictory results have been reported by Pekhlivanov et al [ 60 ] and Jalilian et al [ 61 ], who noted increased leptin concentrations in PCOS patients.…”
Section: Discussionsupporting
confidence: 93%
“…The high values of WHR observed in this study are in agreement with a previous study done by Mutib and coworkers (26) on Iraqi PCOS women. Their study reported a significant difference in BMI, waist and hip circumferences and waist/hip ratio between PCOS women and healthy control group (27). In this study, the waist circumferences and waist/hip ratios were higher among Saudi Arabian women with PCOS compared with those in the healthy control group.…”
Section: Discussionsupporting
confidence: 41%
“…On the other hand, no correlation was reported between BMI and PCOS in a few other clinical and research studies (29)(30)(31). In addition, some findings showed that women with low BMI (i.e., lean) showed a stronger association with PCOS than obese women (27,30).…”
Section: Discussionmentioning
confidence: 94%
“…Some of these changes are characterized by increased serum concentrations of leptin, tumor necrosis factor (TNF)-α and interleukin (IL)-6 and by the reduced production of adiponectin (4)(5)(6). The relationship between PCOS and adipokines is controversial because this endocrinemetabolic disorder is often associated with an increased body fat percentage (7). However, there is controversy about adiponectin role in inflammation since its plasma concentration decreases in some inflammatory diseases, for example in obesity and PCOS, and increases under some other inflammatory conditions -rather than decreased -in classic chronic inflammatory/autoimmune diseases that are unrelated to increased adipose tissue, such as rheumatoid arthritis type 1 diabetes (8).…”
Section: Introductionmentioning
confidence: 99%